Asset and Debt Management Ratios in Bankruptcy Prediction - Evidence from India - Ramesh, Adithi; Senthil Kumar, C. B. (Indian Journal of Finance, 2018)
The purpose of this paper was to attempt an evaluation of effectiveness of asset and debt management ratios as an analytical tool to predict corporate bankruptcy. Earlier, Altman (1968), Ohlson (1980), and Zmijewski (1984) analyzed the power of financial ratios in predicting bankruptcy. This study is an extension of the literature. A set of variables that acted as the best measure of asset and debt management of a corporate were investigated and multiple discriminant analysis was applied. It was found that the new model proved to be significant in predicting bankruptcy.